Brief bibliometric study on solidarity economy - Barbosa Pérez, Ehytder Mario; Vargas Pacheco, Henry; Gómez Rodríguez , Dustin Tahisin (Cooperativismo & Desarrollo, 2020)
In this study, we carried out a bibliometric analysis of scientific production (282 articles) of the solidarity economy category in the 2010-2019 in the Web of Science database. An increase in the number of publications on Solidarity Economy until 2017 was identified. Most documents were scientific (76%), followed by book chapters. The authors with the highest number of publications were S. Calvo and A. Morales. In contrast, theorganizations with the highest production were the Cooperative University of Colombia and the University of Bournemouth. The country with the highest production was Brazil, and Colombia is in seventh place, which confirms the need to expand and enrich its scientific heritage vis-à-vis the solidarity economy.
Keywords: associativity; bibliometry; economic development; solidarity economy; bibliometric analysis